Salt Tolerance in Indian Mustard (Brassica juncea (L.) Czern and Coss) - kumar, D; Rathore, Neetu (Annals of Arid Zone, 2016)
Relative. salt tolerance potential of tim Indian mustard (Brassica juncea (L.) Czern and Coss) genotypes assessed at salinity levels of 2.1 (control), 6.8 and 10.5 dS m-1 revealed that seed yield with 61.3% reduction at the highest salinity over control was severely affected. However, 1000-seed weight with 22.6% . reduction at the same salinity .level was the most resistant trait under such conditions. Amongst the genotypes, SAL-3 with minimum reduction in seed yield at the highest salinity over control (54%) and the highest mean susceptibility iridex (MSI) value (7.0) was the most tolerant. On the contrary, CSTR-338-1 with maximum seed yield reduction (74%) at the highest salinity over control and least MSI (5.2) value was the most sensitive. Tolerant genotypes were typically characterized by several fold wider KINa ratio at the salinity level of 10.5’ dS m-l over its preceding EC level of 6.8 dS m-l . Our results revealed that salt tolerant genotypes ,could be conveniently screened’ by a proportion of wider KINa ratio at the threshold salinity over its preceding salinity level.